Potential antiviral activity of Plexaurella regia on the replication of herpes simplex virus type 1 - Paixão, Izabel Christina Nunes de Palmer; Giongo, Viveca; Mello, Camilly Pestana Pires de; Mateini, Felipe; Barbosa, Juliana; Barbosa, Jussara Pinheiro; Fleury, Beatriz Grosso; Castro, Clovis Barreira e; Pinto, Angelo da Cunha (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Latency and resistance of acyclovir-resistant strains of Herpes simplex virus type 1 (HSV-1) have been associated with serious sequelae in immunocompromised individuals, such as AIDS patients. Consequently, the search for new substances with anti-HSV activity is both necessary and urgent. Objective: To investigate whether extracts obtained from Plexaurella spp can be used in preclinical studies of drugs against herpes simplex virus type 1. Methods: Cell viability and inhibitory drug concentrations as screening tests were used to investigate ethyl acetate and dichloromethane extracts from Plexaurella spp as antivirals. Results: The results of viability assays demonstrated that extracts from Plexaurella regia and Plexaurella grandiflora showed less cytotoxicity, but only Plexaurella regia reached a very expressive CC50 value. In antiviral assays, Plexaurella regia showed an even more significant result of effective concentration (EC50) and therapeutic index (<2.5 μg/mL and 51.6 μg/mL, respectively) compared with acyclovir (ACV). Conclusion: These results demonstrated that extracts from corals have anti-herpetic activities and could contribute towards new strategies to stop the increasing incidence of resistance in herpes-related diseases.